The psychopathologies of cognitive capitalism : Part Two - Neidich, Warren (Berlin : Archive Books, 2013)
Essays by Ina Blom ; Arne De Boever ; Pascal Gielen ; Sanford Kwinter ; Maurizio Lazzarato ; Karl Lydén ; Yann Moulier Boutang ; Warren Neidich ; Matteo Pasquinelli ; Alexei Penzin ; Patricia Reed ; John Roberts ; Liss C. Werner ; Charles T. Wolfe
Published on the occasion of "The Psychopathologies of Cognitive Capitalism: Part Two" at ICI Berlin, this book collects the papers that were presented during the first part of the conference Los Angeles in November 2012.
boek
Keywords: Neidich, Warren